2020
DOI: 10.48550/arxiv.2003.08439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kibble-Zurek behavior in disordered Chern insulators

Lara Ulčakar,
Jernej Mravlje,
Tomaž Rejec

Abstract: Even though no local order parameter in the sense of the Landau theory exists for topological quantum phase transitions in Chern insulators, the highly non-local Berry curvature exhibits critical behavior near a quantum critical point. We investigate the critical properties of its real space analog, the local Chern marker, in weakly disordered Chern insulators. Due to disorder, inhomogeneities appear in the spatial distribution of the local Chern marker. Their size exhibits power-law scaling with the critical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The experimental observations of a nonzero Hall drift [1,27] thus inspired a plethora of studies [15,25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Nonunitary effects, including thermal baths [28,30] and dephasing noise [34], were shown to stabilize a nearly quantized Hall conductance, in much the same way that a diagonal ensemble of unitary time evolution would predict [42,43].…”
Section: Introductionmentioning
confidence: 85%
“…The experimental observations of a nonzero Hall drift [1,27] thus inspired a plethora of studies [15,25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Nonunitary effects, including thermal baths [28,30] and dephasing noise [34], were shown to stabilize a nearly quantized Hall conductance, in much the same way that a diagonal ensemble of unitary time evolution would predict [42,43].…”
Section: Introductionmentioning
confidence: 85%
“…Among the most prevalent of these topological markers is the so-called Chern marker [25]. Since the Chern marker does not require translational invariance, it has been used to probe topological phases and topological phase transitions of inhomogeneous systems [26][27][28][29][30][31][32][33]. Recent work analysed the non-equilibrium dynamics of the Chern marker for a system undergoing a quantum quench and found that topological currents arise within the system [34].…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that, as in the half-filling case, the sign of C depends on the ground state symmetry breaking sector. Notice also that these local fluctuations of C, which are caused by a spontaneous breaking of translational symmetry, are reminiscent of those induced by quenched disorder in a gauge-induced Chern insulator [42].…”
mentioning
confidence: 95%